## Wednesday, February 16, 2011

### Kathleen's Scribepost for February 16, 2011

Multiplying Binomials by Monomials

Today, we started out with an equation to solve.

- ( x + 7 )

How to solve:

= -1 ( x + 7 )
= -1x + (-1)(7)
= -x -7

Next equation:
2(3x + 4)

Solve:
= 2(3x)+2(4) or 3x+4+3x+4
= 6x + 8

This is called distributive property.

The trick to answering an equation is to look at the signs very carefully.

Signs will always confuse you.

(-)(-) Two negatives makes a positive.
(-)(+) One negative makes a negative.
(+)(+) Positives makes a positive.

Example:

-2 ( 3x - 4 )

= -2(3x) + -2(4)
= -6x - 8

2x ( 3x + 4 )

= 2x(3x) + 2x(4)
= 6x ² + 8x

Another way to write this is:

(2)(3)(x)(x) + (2)(4)(x)

Which equals the same thing.

Now a model can be shown:

Another equation is:

-4x (2x - 3y +5)

= -4x(2x) + (-4x)(-3y) + (-4x)(5)
= (-4)(2)(x)(x) + (-4)(-3)(x)(y) + (-4)(5)(x)
= -8x ²+ 12xy -20x

Now one more step is missing; which is the equation has to be in alphabetical order for final answer.

= -8x ²- 20x + 20xy

Homework:

CYU 2 & 3
Practice Odd or Even
2 Apply
Extend - 19 & 20 or 20 & 21
Homework Book 7.2
Extra Practice 7.2